Bishop's University, 1843-1970 - Nicholl, Christopher, 1922- (Published for Bishop's University by McGill-Queen's University Press, 1994)
Most Canadian universities were created in response to society's perceived need for men and women trained in the professions, or at least prepared to take up gainful employment that contributes to the national economy. In contrast, Bishop's was inspired by John Henry Newman's idea of the university as an academic community in which undergraduates might form their opinions and learn to defend them by living among those whose interests and competence include a wide range of disciplines. The goal of such an education is to produce what Newman calls a "philosophical habit of mind" an ability to think which, being independent of any particular subject, is the instrument of all. Nicholl traces the development of this defiantly Anglican transplant in an American-settled corner of a largely French-speaking province into an autonomous, Canadian, and increasingly bilingual university. He reveals how its early growth was hampered by the financial stringency which resulted from its denominational character and resolutely anti-utilitarian philosophy. This penury was relieved under Principal McGreer (1922-47), who broke the denominational tie and persuaded a number of the financial and industrial leaders of Quebec's English-speaking community that sound and liberal education provided a good foundation in life for those who hoped to be useful in more than a purely technical sense. Under McGreer Bishop's achieved not only financial stability but also academic autonomy, which lasted until the 1960s when the advent of government financing and an interventionist Ministry of Education placed the university's philosophy of education at risk. Tracing the academic, administrative, and physical growth of Bishop's through periods of crisis and calm, Nicholl concludes optimistically that Bishop's will be able to maintain its academic traditions, although conceding that by 1970 the founders' idea of the university as a moral enterprise was no longer viable.